Differentiation of Cardiomyocytes from Human Pluripotent Stem Cells Using Monolayer Culture - Batalov, Ivan (Biomark Insights, 2015)
Human pluripotent stem cells (PSCs) are a promising cell source for cardiac tissue engineering and cell-based therapies for heart repair because they can be expanded in vitro and differentiated into most cardiovascular cell types, including cardiomyocytes. During embryonic heart development, this differentiation occurs under the influence of internal and external stimuli that guide cells to go down the cardiac lineage. In order to differentiate PSCs in vitro, these or similar stimuli need to be provided in a controlled manner. However, because it is not possible to completely recapitulate the embryonic environment, the factors essential for cardiac differentiation of PSCs in vitro need to be experimentally determined and validated. Since PSCs were first developed, significant progress has been made in optimizing techniques for their differentiation toward cardiomyocytes. In this review, we will summarize recent advances in these techniques, with particular focus on monolayer-based methods that have improved the efficiency and scalability of cardiomyocyte differentiation.